Medication adherence 1 month after hospital discharge in medical inpatients. Issue 2 (February 2016) - Mitchell, B.; Chong, C.; Lim, W. K.
Abstract : Background: The rate of medication non‐adherence has been consistently reported to be between 20 and 50%. The majority of available data comes from international studies, and we hypothesised that a similar rate of adherence may be observed in Australian patients. Aims: To determine the rate of adherence to medications after discharge from acute general hospital admission and identify factors that may be associated with non‐adherence. Methods: A prospective cohort study of 68 patients, comparing admission and discharge medication regimens to self‐reported regimens 30–40 days after discharge from hospital. Patients were followed up via telephone call and univariate and multivariate binary logistic regression used to determine patient factors associated with non‐adherence. Results: In all, 27 of 68 patients (39.7%) were non‐adherent to one or more regular medications at follow up. Intentional and unintentional non‐adherence contributed equally to non‐adherence. Using multivariate analysis, presence of a carer responsible for medications was associated with significantly lower non‐adherence (odds ratio (OR) 0.20 (0.05–0.83), P = 0.027) when adjusted for age, co‐morbidities, chemist blister pack and total number of discharge medications. Conclusions: Non‐adherence to prescription medications is suboptimal and consistent with previous overseas studies. Having a carer responsible for medications is associated with significantly lower rates of non‐adherence. Understanding patients' preferences and involving them in their healthcare may reduce intentional non‐adherence.